Exploring Middle School Teachers' Job Demands and Job Resources during COVID-19 - Lang Juana M.; Valk Joshua (Sciendo, 2023)
Introduction: The study aimed to explore teachers' general working conditions, job demands and resources, and teachers' general well-being in four middle schools in the Southeastern U.S during COVID-19.